Tinospora cordifolia GCMS profiling and cytotoxic effect on HCT 116- In vitro assay (Advances in Applied Biological Research, 2025)
An assessment of Tinospora cordifolia extract’s (TCE) antimicrobial and antioxidant  properties was undertaken in light of its possible application as cytotoxic against  HCT116. Compounds from the stem were Soxhlet extracted with ethyl acetate  and identified through GCMS. Antibacterial, antioxidant and HCT cytotoxicity  of extract was studied by conventional standard methods. The GC–MS profile  highlights a chemically diverse phytochemical composition, with both major and  minor compounds potentially responsible for natural antimicrobial and antioxidant  agent. The extract has broad spectrum antibacterial activity at concentration  dependent manner against both Gram positive and negative clinical pathogens  with relative inhibition 83 to 107%. Among the tested antioxidant assay the extract  showed the strongest DPPH scavenging with an IC₅₀ value of 12.07 µg/mL, which,  although higher than the standard ascorbic acid. Treatment of HCT116 colorectal  carcinoma cells with TCE resulted in a dose-dependent reduction in cell viability.  Nonlinear regression analysis of the MTT assay revealed an IC₅₀ value of 359  µg/ml, with viability decreasing from ~80% at 300 µg/ml to
Keywords: Alkaloid; Anticancer; Colon cancer; Antioxidant; Antibacterial